MANFAAT ANALOGI DALAM HUKUM PIDANA UNTUK MENGATASI KEJAHATAN YANG MENGALAMI MODERNISASI - Aris Hardinanto (Universitas Airlangga, 2016)
The development of information technology and bring a significant impact on the development of society and the law. In the field of criminal law, appear various types of crimes recently that never existed in the laws of criminal law (CRIMINAL CODE), because by the framers, haven't gotten around to think about before. The consequences are many terms in the PENAL CODE which, if interpreted narrowly made the CRIMINAL CODE left behind by the times. To overcome stiffness in interpreting CRIMINAL CODE, then the judge is given the authority to interpret broadly known by the method of interpretation of the law. Methods of interpretation of law in the criminal law is a method of grammatical interpretation, history, teleologis, systematic, and extensive or restrikif. Legal scholars have different opinions on the interpretation of the extensive and analogy. Some legal scholars distinguish but there are who equate. The difference of views as well as to be whether the analogy application of analogy in the criminal law. The analogy has a benefit as solution addressing the stiffness of judges in interpreting the provision in the Criminal Code which have not had time unthinkable by the framers of the CRIMINAL CODE as the impact of the development of science and technology.